A Relative Examination of the Enchantment of William Blake and Rabindranath Tagore: Exploring Mysticism in the Works of William Blake and Rabindranath Tagore (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The strands of mysticism can be seen in practically all the romantic artists of the world regardless of the language they write in or the age they live in. In some romantic writers the spiritualist components stay torpid as they care more about different wonders which is of quick worry to them. This paper talks about the idea and impression of mysticism in progress of the occidental writer William Blake and the oriental artist Rabindranath Tagore. Brought into the world in various grounds they appeared to share an otherworldly proclivity. William Blake's works, however to a great extent Biblical in its symbolism, is whole-world destroying in style and degree. In Indian magical idea, Tagore offers a framework wherein the belief in a higher power of the Bhagavad Gita, the transcendentalism of the Vedas, the Upanishads, the mysticism of the Bauls and the philosophical standards of Vaishnavism and Sufism exist in amalgamation.